Sustained efforts and collective claims: the social influence of the vegan movement from 1944 to present - Troncale Rawls, Shannon (Kansas State University, 2010)
Following a strict form of vegetarianism, vegans adopt a philosophy and practice a lifestyle that seeks to eliminate the use of all animal products and by-products in any form. Although vegetarian diets have been popular in many cultures for centuries, a more organized and defined version of veganism as we know it today did not emerge until the mid-1940s. Although the origins and nature of vegetarianism and veganism have been researched in depth for decades, this lifestyle has scarcely been evaluated as a social movement. Therefore, I seek to fill this gap in knowledge and describe veganism as a social movement and evaluate its social effects. I have gathered historical and sociological data and theories from a variety of sources. I combine this data in order to thoroughly illustrate the history, nature, and future of vegans as a social movement and show how it has contributed to social change. The sociological definitions of what constitutes a social movement as described by Charles Tilly and Sidney Tarrow will illustrate the many ways vegans can be viewed as a social movement. A synthesis of these two social scientists’ definitions in the analysis of vegans as a social movement will show that vegans meet both Tilly and Tarrow’s criteria for a social movement. I will use these criteria as a framework to show how vegans’ activity and growth fit into Tilly and Tarrow’s theoretical outline for what constitutes a social movement. Further, I use other evidence such as polls and news articles in order to support this idea, showing the movement behaviors of vegans in Western culture.
Keywords: Veganism; Vegan; Social movements; Vegetarianism; Sociology, General (0626)